Arabidopsis GAAP1 and GAAP3 Modulate the Unfolded Protein Response and the Onset of Cell Death in Response to ER Stress - Guo, Kun; Wang, Wei; Fan, Weiwei; Wang, Zhiying; Zhu, Manli; Tang, Xiaohan; Wu, Wenting; Yang, Xue; Shao, Xinghua; Sun, Yue; Zhang, Wei; Li, Xiaofang (Frontiers in Plant Science, 2018)
The function of human Golgi antiapoptotic proteins (GAAPs) resembles that of BAX inhibitor-1, with apoptosis inhibition triggered by intrinsic and extrinsic stimuli. However, little is known about the function of GAAP-related proteins in plants. Here, we studied Arabidopsis GAAP1 and GAAP3 and found that they were localized on the cellular membrane, including the endoplasmic reticulum (ER) membrane. The function of GAAP1/GAAP3 in ER-stress response was tested, and results showed that single or double mutation in GAAP1 and GAAP3 reduced plant survival and enhanced cell death under ER stress. The expression of both genes was induced by various abiotic stress signals. Quantitative real-time polymerase chain reaction analysis showed that GAAP1/GAAP3 level affected the expression pattern of the unfolded-protein response (UPR) signaling pathway genes upon prolonged ER stress. The mutation in both GAAP1 and GAAP3 genes promoted and enhanced UPR signaling when confronted with mild ER stress. Moreover, GAAP1/GAAP3 inhibited cell death caused by ER stress and promoted plant-growth recovery by turning down inositol-requiring enzyme 1 (IRE1) signaling after ER stress had been relieved. Co-immunoprecipitation and BiFC assays showed that GAAP1/GAAP3 interacted with IRE1. These data suggested that GAAP1/GAAP3 played dual roles in the negative regulation of IRE1 activity and anti-programmed cell death.